A computational journey in the CH2O2S land: an accurate rotational and ro-vibrational analysis of the sulfene molecule and the O, S- and O, O-monothiocarbonic acids. (17th October 2020) - Alessandrini, S.; Dell'Isola, V.; Spada, L.; Barone, V.; Puzzarini, C.
Abstract : Molecules containing sulfur play an important role in atmospheric chemistry, but their reactivity in such environment is far from being well characterised. Therefore, important transient species might still have to be disclosed. In this regard, this paper aims at contributing to this field by means of the computational spectroscopic characterisation of potentially relevant atmospheric species, such as the CH 2 O 2 S isomers. Based on our computational investigation, the most stable species are the carbonothionic O, S- and O, O-acids. In addition to them, the sulfene molecule has also been considered. For all these species, the equilibrium structure and the corresponding rotational constants have been accurately evaluated using a coupled-cluster-based composite approach. All the other parameters required for the simulation of the rotational and ro-vibrational spectra have been obtained by exploiting density functional theory. GRAPHICAL ABSTRACT: